Genome-wide identification of the WRKY gene family in Camellia oleifera and expression analysis under phosphorus deficiency - Su, Wenjuan; Zhou, Zengliang; Zeng, Jin; Cao, Ruilan; Zhang, Yunyu; Hu, Dongnan; Liu, Juan (Frontiers in Plant Science, 2023)
Camellia oleifera Abel. is an economically important woody edible-oil species that is mainly cultivated in hilly areas of South China. The phosphorus (P) deficiency in the acidic soils poses severe challenges for the growth and productivity of C. oleifera. WRKY transcription factors (TFs) have been proven to play important roles in biological processes and plant responses to various biotic/abiotic stresses, including P deficiency tolerance. In this study, 89 WRKY proteins with conserved domain were identified from the C. oleifera diploid genome and divided into three groups, with group II further classified into five subgroups based on the phylogenetic relationships. WRKY variants and mutations were detected in the gene structure and conserved motifs of CoWRKYs. Segmental duplication events were considered as the primary driver in the expanding process of WRKY gene family in C. oleifera. Based on transcriptomic analysis of two C. oleifera varieties characterized with different P deficiency tolerances, 32 CoWRKY genes exhibited divergent expression patterns in response to P deficiency stress. qRT-PCR analysis demonstrated that CoWRKY11, -14, -20, -29 and -56 had higher positive impact on P-efficient CL40 variety compared with P-inefficient CL3 variety. Similar expression trends of these CoWRKY genes were further observed under P deficiency with longer treatment period of 120d. The result indicated the expression sensitivity of CoWRKYs on the P-efficient variety and the C. oleifera cultivar specificity on the P deficiency tolerance. Tissue expression difference showed CoWRKYs may play a crucial role in the transportation and recycling P in leaves by affecting diverse metabolic pathways. The available evidences in the study conclusively shed light on the evolution of the CoWRKY genes in C. oleifera genome and provided a valuable resource for further investigation of functional characterization of WRKY genes involved to enhance the P deficiency tolerance in C. oleifera.